Modeling Optimal Time Allocation for Work and Personal Life at The National Level (Case in Lithuania) - Tauraite, Viktorija; Lydeka, Zigmas (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The article deals with the acute phenomenon in the 21st century – the distribution of time for work and personal life. Employed people in the modern society are most frequently faced with problems of work-life conflict. For this reason, this article primarily focuses on determination of optimal time allocation for work and personal life. First, this study analyzes the theoretical aspects of time allocation for work and personal life. Subsequently, a model for optimal time allocation for work and personal life is presented and the research methodology is substantiated. The model is realized by solving the multicriterial (target) optimization problem using weighting coefficients and priority methods and performing sensitivity analysis. This model is composed based on the employed population of Lithuania, but it can be adapted to other countries as well. In this case, the original questionnaire and time diary data should be obtained in the country under investigation. The results of the empirical research carried out showed that the population in Lithuania in 2017 begins to devote more time to personal life compared to 2003. Nevertheless, employed populations do not optimally allocate time between work and private life. For this reason, the article provides recommendations for employed people in Lithuania seeking to balance distribution of time for work and personal life, taking into consideration the current and desired monthly net wages.